¿Moro invasor o hermano revolucionario? - Josefa Alcolea Escribano (Cahiers de Civilisation Espagnole Contemporaine)
This article analyses the image Moroccans and Morocco had in the anarchist-syndicalist Valencian newspaper Fragua Social, themeans of expression used by the CNT (Work National Confederation) in the Eastern regions between 1936 and 1939. Without denying the xenophobic stereotypes used by the Confederation press during the Spanish Civil War, it is necessary to clarify them because they coexisted with other, more condescending or even positive images of Moroccan people. Negative images of Moroccans were a kind reference point to build up a stereotyped cliché of the opposing side so as to expel them from the national force, and to get help from abroad. Likewise, positive images tried to avoid Moroccans joining Franco's side or deserting. They also strengthened a Spanish reformist program, where Morocco could also be included.